Solution-Processable Hole-Transporting Polymers: Synthesis, Doping Study and Crosslinking Induced by UV-Irradiation or Huisgen-Click Cycloaddition - Caldera-Cruz, Enrique; Zhang, Kenan; Tsuda, Takuya; Tkachov, Roman; Beryozkina, Tetyana; Kiriy, Nataliya; Voit, Brigitte; Kiriy, Anton (Advanced Materials Interfaces, 2022)
A pair of hole-conducting polymers comprising 3,6-linked carbazole and meta-linked anisole derivatives having solubilizing moieties to enable their solution processability, and complementarily reactive side-groups (azide and alkyne) for cross-linking, are synthesized and characterized. The polymers can be cross-linked either by thermal annealing at relatively low temperatures in the 85–110 °C range, or by UV irradiation. A general applicability of the latter for a photolithographic patterning of the hole conducting polymer is proven. The polymers have an ionization potential (IP) of 5.8 eV, close to the IP of a small molecule hole-conductor tris(4-carbazoyl-9-ylphenyl)amine (TCTA). In combination with a strong dopant hexacyano-trimethylene-cyclopropane (CN6CP), but not with commercial 2,3,5,6-tetrafluoro-7,7,8,8-tetracyanoquinodimethane (F4TCNQ), the polymers can be efficiently p-doped to increase their conductivity by 5–6 orders of magnitude, as measured in devices with a lateral setup. Taken together, these characteristics suggest that the synthesized polymers are promising candidates for their use in solution-processable organic light-emitting diodes as hole-injection layer and hole-transporting layer materials, which will be verified in the upcoming work.
CRIS-Team Scopus Importer:2022-04-14
Keywords: conductivity; cross-linking; doping; hole-injection layers; hole-transporting layers; solution-processable semiconductors